Benefits of the fiber optic versus the electret microphone in voice amplification - Kyriakou, Kyriaki; Fisher, Hélène R (My University, 2013)
Voice disorders that result in reduced loudness may cause difficulty in communicating, socializing and participating in occupational activities. Amplification is often recommended in order to facilitate functional communication, reduce vocal load and avoid developing maladaptive compensatory behaviours. The most common microphone used with amplification systems is the electret microphone. One alternate form of microphone is the fiber optic microphone.
Keywords: Electrical systems; Microphones; Optics; Voice disorders